Analisis Kemampuan Computational Thinking (CT )Peserta Didik Kelas VIII SMP Negeri 1 Bangkinang Kota - Ahmadi, Devila Laura Alviona; Astuti; Zulfah; Bahasa Indonesia, Bahasa Indonesia; Bahasa Indonesia (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This research aims to analyze the CT abilities of class VIII students at SMP Negeri 1 Bangkinang Kota. CT ability is an ability that students must have and to find out to what extent these CT abilities have developed and been fulfilled by students. This research is a qualitative descriptive research. The research subjects were all class VIII students, totaling 36 students. The data collect ion techniques used were interviews and tests. The results of this research can be concluded that the high category (KT) subjects can understood the question information correctly in worked on CT ability questions, can answered questions according to the CT ability indicators, answer correctly and can also made conclusions from the answers obtained and check again. to ensure the corrected of the answer. Likewise, subjects in the medium category (KS) are quite good at found information from the questions, but do not understood the answers to the questions themselves. Medium category students can also made conclusions from the answers they get. Meanwhile, low category subjects (KR) were unable to understood the questions, found the right information and drew conclusions when solving the CT ability test questions.